Consumption of cherries as a strategy to attenuate exercise-induced muscle damage and inflammation in humans - Rabello de Lima, Leonardo Coelho [UNESP]; Assumpcao, Claudio de Oliveira; Prestes, Jonato; Denadai, Benedito Sergio [UNESP] (Aula Medica Ediciones, 2015)
Background: exercise-induced muscle damage (EIMD) is a multifactorial phenomenon that induces muscle function loss because of mechanical and immune stressor stimuli. This immunological stress is mostly caused by inflammation and increased oxidative status. Cherries are fruits that contain a phenolic compound known as anthocyanin, which serves as a pigment in natura. However, research suggests this pigment might provide a potent antioxidant and anti-inflammatory strategy when consumed by humans. Objectives: the aim of this study was to critically review the literature on cherry consumption focusing on identifying protective strategies against EIMD conferred by it. Methods: a research was performed in PubMed database. This review presents the results about cherry consumption and EIMD. Results: the articles identified in this review support the notion that tart cherry consumption attenuates EIMD symptoms after intense exercise bouts. This attenuation seems to be related to the antioxidant and anti-inflammatory properties of anthocyanins and other phenolic compounds present in tart cherries. Conclusion: daily consumption of tart cherries may attenuate inflammatory and oxidative responses to EIMD, leading to faster recovery after exercise bouts.
Keywords: Cherries; Muscle damage; Flavonoids; Anthocyanins; Recovery